(untitled) (Confluenţe Bibliologice, 2019)
The paper presents the ways of professional training in the USARB Scientiﬁc Library, which is the priority element that eﬀectively ensures the success of an institution and that the best library services depend on the good training and continuous training of its staﬀ.